Contribution of social support co-workers and social self concept to conditions of school counselor burnout - Suci Habibah; Herman Nirwana; Afdal Afdal (International Conferences on Educational, Social Sciences and Technology)
This study aims to examine the contribution of social support co-workers and social self-concepts together to school counselor burnout conditions. This research uses quantitative method of correlation descriptive type. The population of the research is the State Senior High School counselor of Pekanbaru City. The sample numbered 52 people school counselors were assigned with sampling technique total sampling. The instruments used are the “Burnout Scale” with reliablity 0,976, “Social Support Co-workers Scale” with reliability 0,959, and “Social Self-Concept Scale” with reliablity 0,934. The research data were analyzed using multiple regression. The research findings show that there is contribution of social support of co-workers and social self concept to burnout condition equal to 55.7%. The implications of this research on guidance and counseling will be discussed.